Industrial layout reconstruction, the role of local government and variation of pollution distribution in China. Issue 4 (2nd October 2018) - Ge, Liming; Qin, Bingtao; Li, Shang
ABSTRACT: In recent years, high-polluting industries have been gradually shifted from the eastern developed regions to the central and western underdeveloped regions in China. Certain environmental regulations have been in place accordingly in various regions, but the pollution in the central and western regions has risen sharply. Based on the data of interprovincial panel in China from 2006 to 2015, this paper calculates high-pollution industry dynamic agglomeration index, environmental pollution agglomeration index and relative environmental regulation intensity index, and uses Generalized Method of Moments to carry out the regression analyses of the whole samples, regional heterogeneity and temporal heterogeneity. The results show that there is an inverted U-shaped relationship between relative environmental regulation and environmental pollution concentration in China. The concentration degrees of industrial wastewater pollution and industrial waste gas pollution are deepened, which are mainly caused by the transfer of highly polluting industries. However, the concentration of industrial solid waste pollution caused by the transfer is not obvious. Furthermore, the deepening of industrialization intensifies the concentration of regional environmental pollution. Environmental Kuznets Curve does exist in China, but it is not significant. The increase of labor cost and quality will reduce the concentration of environmental pollution.